A Case Study at a Private University of Jepara Central Java Indonesia: Examining Students’ Attitudes toward Online English Teaching - Haryanto, Haryanto; Effendi, Dwi Erlin (Technium Social Sciences Journal, 2023)
The utilization of media, the nature of communication, and the learning preferences of the students can all be considered in online learning models. This study attempts to investigate how students interact with and view English classes taught online. The respondent characteristics, educational media, and student learning preferences were the main topics of the study. The study was carried out at UNISNU Central Java Indonesia, a private university. Purposive sampling techniques were used to choose the 206 students from the Faculty of Education and Teacher Training who had registered for the English II course as the population. 166 students who responded to the survey using a Google Form make up the samples. The findings indicate that the respondents favor using live or recorded video to present the topic. Classroom activities include creating videos and presentations for assignments, posting the recorded presentations to the university’s online platform, and more. Online lectures continue to receive inadequate feedback from students. However, despite a number of drawbacks, online learning is still active. The leadership of the institution must also keep an eye on the implementation of this online learning so that it can be frequently evaluated.